2013
DOI: 10.1158/1078-0432.ccr-12-1662
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathways: P-Rex in Cancer

Abstract: P-Rex proteins are Rho/Rac guanine nucleotide exchange factors that participate in the regulation of several cancer-related cellular functions such as proliferation, motility, and invasion. Expectedly, a significant portion of these actions of P-Rex proteins must be related to their Rac regulatory properties. In addition, P-Rex proteins control signaling by the phosphoinositide 3-kinase (PI3K) route by interacting with PTEN and mTOR. The interaction with PTEN inhibits its phosphatase activity, leading to AKT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 40 publications
(83 reference statements)
1
32
0
Order By: Relevance
“…Furthermore, ectopic expression of mutant PREX2, which was present in patients with melanomas, accelerated the tumor formation of immortalized human melanocytes in vivo (15). In addition, overexpression of PREX2 has been revealed to be associated with the poor overall survival of patients with breast cancer (22). The present study identified that the expression of PREX2 was upregulated in HCC tissues and cell lines compared with adjacent normal tissues and normal liver cell lines.…”
Section: Discussionsupporting
confidence: 50%
“…Furthermore, ectopic expression of mutant PREX2, which was present in patients with melanomas, accelerated the tumor formation of immortalized human melanocytes in vivo (15). In addition, overexpression of PREX2 has been revealed to be associated with the poor overall survival of patients with breast cancer (22). The present study identified that the expression of PREX2 was upregulated in HCC tissues and cell lines compared with adjacent normal tissues and normal liver cell lines.…”
Section: Discussionsupporting
confidence: 50%
“…Recently, the overexpression of P-Rex proteins has been linked to poor patient outcome in breast cancer, since it may facilitate metastatic dissemination of prostate cancer cells (16). Whole-genome sequencing identified PREX2 as a significantly mutated gene in melanoma, suggesting that PREX2 may also be involved in the development and progression of melanoma (18).…”
Section: Discussionmentioning
confidence: 99%
“…However, PTEN is frequently mutated or its activity is downregulated in human cancer (13,14). Phosphatidylinositol-3,4,5-trisphosphate-dependent Rac exchanger factor 2 (PREX2) is a regulator of the small guanosine triphosphatase Rac, and has recently been reported to act as an inhibitor of PTEN (15,16). PREX2 is able to inhibit the activity of PTEN by directly binding to PTEN through its guanine nucleotide exchange factor domains.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations